In situ CO2 gas-exchange in fruits of a tropical tree, Durio zibethinus Murray - Ogawa, Kazuharu; Furukawa, Akio; Hagihara, Akio; Abdullah, AhmadMakmom; Awang, Muhamad (Springer Science and Business Media LLC, 1995)
We examined the in situ CO2 gas-exchange of fruits of a tropical tree, Durio zibethinus Murray, growing in an experimental field station of the Universiti Pertanian Malaysia. Day and night dark respiration rates were exponentially related to air temperature. The temperature dependent dark respiration rate showed a clockwise loop as time progressed from morning to night, and the rate was higher in the daytime than at night. The gross photosynthetic rate was estimated by summing the rates of daytime dark respiration and net photosynthesis. Photosynthetic CO2 refixation, which is defined as the ratio of gross photosynthetic rate to dark respiration rate in the daytime, ranged between 15 and 45%. The photosynthetic CO2 refixation increased rapidly as the temperature increased in the lower range of air temperature Tc (Tc <28.5 °C), while it decreased gradually as the temperature increased in the higher range (Tc ≥28.5 °C). Light dependence of photosynthetic CO2 refixation was approximated by a hyperbolic formula, where light saturation was achieved at 100 μmol m-2 s-1 and the asymptotic CO2 refixation was determined to be 37.4%. The estimated gross photosynthesis and dark respiration per day were 1.15 and 4.90 g CO2 fruit-1, respectively. Thus the CO2 refixation reduced the respiration loss per day by 23%. The effect of fruit size on night respiration rate satisfied a power function, where the exponent was larger than unity.